Increased Surgical Site Infection Rates following Clindamycin Use in Head and Neck Free Tissue Transfer. (February 2016) - Pool, Christopher; Kass, Jason; Spivack, John; Nahumi, Nadav; Khan, Mohemmed; Babus, Lenard; Teng, Marita S.; Genden, Eric M.; Miles, Brett A.
Objective: The development of surgical site infections (SSIs) can put the viability of free tissue transfer reconstructions at risk, often resulting in considerable postoperative morbidity and prolonged hospitalization. Current antibiotic prophylactic guidelines suggest a first- or second-generation cephalosporin with metronidazole for clean-contaminated cases and recommend clindamycin as an alternative choice in penicillin-allergic patients. This study was designed to examine the rates of postoperative infection associated with prophylactic antibiotic regimens, including patients receiving clindamycin as an alternative due to penicillin allergy. Study Design: Case series with chart review. Setting: Tertiary academic medical center. Subjects: Patients undergoing major ablative head and neck resection involving the pharynx and oral cavity reconstructed via free tissue transfer. Methods: The sample included patients (n = 266) who underwent free tissue transfer involving the oral cavity and pharynx from 2009 to 2014. Data included demographic data, medical comorbidities, anatomic tumor subsite and surgical procedure, and prophylactic antibiotic regimen. SSI data were examined up to 30 days after the initial surgical procedure. Multivariate logistic regression analysis was performed to determine the overall risk for SSI. Culture data were also reviewed. Results: The data indicated that clindamycin was associated with an approximate 4-fold increased risk for SSI (odds ratio, 3.784; 95% confidence interval: 1.367-10.470 [ P = .010]) after controlling for possible confounding factors. Conclusion: For patients with a true penicillin allergy, we recommend broader gram-negative coverage with alternative antibiotics, such as cefuroxime, when undergoing free tissue transfer in the head and neck.